Theology of Jesus' teaching objectives toward his listeners - Habeahan, Sampitmo; Amelia, Amelia (Jurnal Pendidikan Agama Kristen (JUPAK), 2023)
A good teacher should know why they teach and what their teaching goals are. One's success in teaching depends on how well they understand and embrace the objectives of their teaching.  The study aims to see what was the purpose of Jesus in conveying His purpose through teaching.  The research design used is descriptive and qualitative. The researcher's reflection found from the sources is the principles of Jesus' purpose in teaching. The results of the study found ten principles of Jesus' purpose in teaching, namely: bringing people to repentance to God, bringing people to have a harmonious relationship with others, increasing true knowledge and understanding, instilling firm belief, fostering good character, taking action, and equipping to serve.